The Determinant Of Pneumonia In Children Under Five Years Old Related To Environmental And Behavioral Factors: Determinant Of Pneumonia - Fitri Rachmillah; La Djabo Buton; Sri Mulyani (STIKes Mandala Waluya Kendari, 2023)
Background: Pneumonia is an acute lower respiratory tract infection that affects the lung tissue (alveoli) and is the single biggest cause of death in children under 5 years old. Several factors cause pneumonia, namely, environmental factors, individual child factors, and behavioral factors . The purpose of this study was to determine the relationship between the physical home environment and behavior with the incidence of pneumonia in children. Methods: This research is an analytic observational study using a Cross Sectional Study design. The population of this study was all mothers who had children aged 0-59 months in 2021 with a total of 1,045 people and 92 samples were obtained from the slovin formula. Results: We found that out of 92 children who had pneumonia, around 34 children( 37 %) had poor lighting, 34 children ( 37 %) had floors that did not meet the requirements, 36 (39.1%) had ventilation that did not meet the requirements, 20 children(21.7%) family members had a habit of smoking inside the house and 37 (30.2%) house windows that were not opened frequently. The results of statistical tests using the Chi-Square Test concluded that lighting, house floors, ventilation, smoking habits and the habit of opening windows were significantly related to the incidence of pneumonia in children with a p-value of 0.00 ; 0.002 ; 0.004; 0.005; 0.015 respectively. Conclusions: Physical environmental factors of the house, lighting conditions, floors and ventilation that do not meet the requirements, and factors of smoking behavior and rarely opening the windows of the house are causes of pneumonia in children.